Serum ?-carotene and Vitamin A Levels in Spontaneous Premature Calves with Respiratory Distress Syndrome - Gul, Yusuf; Gul Baykalir, Burcu (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
The aim of this study was to investigate serum beta-carotene and vitamin A levels in spontaneous premature calves with respiratory distress syndrome. As study material, 25 spontaneously newborn premature calves with respiratory distress syndrome brought to Firat University, Faculty of Veterinary Internal Medicine Clinic for examination and treatment were used. After clinical examination, blood samples received from calves anaylzed spectrometrically for serum beta-carotene and vitamin A levels. Average values of serum beta-carotene and vitamin A were found as 5.22 +/- 0.72 mu g/dL and 16.63 +/- 0.96 mu g/dL respectively. As a result; serum beta-carotene levels in the animals examined here were found to be lower when compared to normal values thus, lack of beta-carotene was considered to increase incidence of premature birth of calf with a multi-faceted etiology.
Respiratorik distres sendromlu spontan prematüre buza?i{dotless}larda serum ?-karoten ve a vitamini düzeyleri
Keywords: Premature; Calves; beta-carotene; Vitamin A